2017
DOI: 10.1007/978-3-319-61615-5_1
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics Are Contaminants of Emerging Concern in Freshwater Environments: An Overview

Abstract: In recent years, interest in the environmental occurrence and effects of microplastics (MPs) has shifted towards our inland waters, and in this chapter we provide an overview of the issues that may be of concern for freshwater environments. The term 'contaminant of emerging concern' does not only apply to chemical pollutants but to MPs as well because it has been detected ubiquitously in freshwater systems. The environmental release of MPs will occur from a wide variety of sources, including emissions from was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
154
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(157 citation statements)
references
References 114 publications
3
154
0
Order By: Relevance
“…Taxation of, or a ban on, single-use plastic shopping bags [17] and bottle return systems [18] are examples of regulatory measures aimed at reducing the general environmental plastic load. Once the plastic has entered the environment, the formation of microplastics is governed by the inherent properties of the plastic and the environmental conditions [19] and thereby practically impossible to mitigate through regulatory measures.…”
Section: Sources Emissions and Regulationmentioning
confidence: 99%
“…Taxation of, or a ban on, single-use plastic shopping bags [17] and bottle return systems [18] are examples of regulatory measures aimed at reducing the general environmental plastic load. Once the plastic has entered the environment, the formation of microplastics is governed by the inherent properties of the plastic and the environmental conditions [19] and thereby practically impossible to mitigate through regulatory measures.…”
Section: Sources Emissions and Regulationmentioning
confidence: 99%
“…The authors found that the science communication part of the IPW program was so effective that it could be used to generate awareness of both plastic debris and POPs. These two types of pollution are interconnected to some extent, since POPs tend to adsorb strongly to plastic debris, making plastic debris a potential vector for environmental transport of POPs [58] (also discussed by [59,60]). Since plastic pollution is often visible (especially for meso-and macroplastic), the environmental risk is more readily perceived than risk from hazardous chemicals such as POPs.…”
Section: Citizen Science and Plastic Pollutionmentioning
confidence: 99%
“…Hence, expectations rose to find solutions and regulations, which could consider all materials summarized by this single term. In contrast, the term "microplastics" refers to a large group of polymers with various chemical and physical properties, originating from different sources and entering the environment via different pathways (see [3,59]). Accordingly, these differences among MP particles apply to their environmental fate and persistence and, consequently, also to their bioavailability and potential impacts to organisms.…”
Section: A Precondition For Regulation: the Definition Of Microplasticsmentioning
confidence: 99%
“…However, currently (micro)plastics enter freshwater systems, and monitoring programs need to evaluate the environmental status quo to develop adequate measures. For instance, the type of (micro)plastic and its entry path into the environment should be considered: Depending on their application, plastics enter the environment as macroplastics, secondary microplastics, or primary microplastics (for definition, see [3]). The regulation of primary MP seems to be closer related to the regulation of chemical pollutants: production, application, and entry into the environment are traceable to a certain extent.…”
Section: General Regulation Options By Environmental Policymentioning
confidence: 99%